Feeding behaviour of biotype E greenbug (Homoptera: Aphididae) and its relationship to resistance in sorghum - Dixon, Alfred G.O.; Bramel-Cox, P.J.; Reese, J.C. (Oxford University Press, 1990)
The feeding behavior of biotype E greenbug, Schizaphis graminum (Rondani), on seedlings of sorghum, Sorghum bicolor (L.) Moench, genotypes with various levels and mechanisms of seedling resistance was examined in a 12-h period with a computerized electronic insect feeding monitor. Results indicated that 7 of the 12 behavioral events monitored (durations of phloem ingestion, probing, and salivation; time to first committed phloem ingestion; and frequencies of occurrence of baseline, probing, and salivation) showed significant quantitative differences among the genotypes. PI266965 and 152388, the two sources with the highest level of seedling antibiosis, had the shortest duration of phloem ingestion (250, 280.5 min); the longest durations of probing (15.2, 15.0 min), salivation (333.2, 314.4 min), and time to first committed phloem ingestion (433.5, 266.4 min); and the highest frequencies of occurrence of baseline (20.3, 22.4), probing (20.1, 22.5), and salivation (26.0, 26.8) of biotype E greenbug, respectively. These events were highly intercorrelated and were about equally related to seedling antibiosis (measured in growth chamber and field) and average damage score (overall resistance) experiments. The most important mechanism that the insect feeding monitor measured was antibiosis.